Zinc: its impact on immune function in children - Kinash, Maria; Boyarchuk, Oksana; Dobrovolska, Lesya (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Based on the analysis of literary sources, this review highlights the main reasons and mechanisms of zinc impact on the development of immunodeficiency conditions in children. The study outlines the importance of zinc homeostasis in the functioning of innate and adaptive immunity. The multifaceted influence of zinc on the activity of the immune system includes the regulation of maturing, differentiation, activity of innate immunity cells (neutrophils, monocytes-macrophages, mast cells, natural killers, dendrite cells) and adaptive immunity cells (T-lymphocytes and B-lymphocytes), activation of interferon synthesis, regulation of the activity of inflammation process, participation in signalling pathways of antigen presentation to the highly specific immune cells, and support of the antioxidant status in the child’s organism. The role of zinc status in antiviral immunity, particularly in COVID-19 infection, is considered. A risk group for the development of zinc deficiency and immunodeficiency conditions is identified.